انتقادات المعاصرين الموجهة إلى حديث اغتسال موسى عليه السلام عرياناً بدعوى مخالفته الذوق العام: دراسة نقدية - الخطاطبة، باسم عبدالقادر أحمد; الوريكات، عبدالكريم أحمد يوسف (الجامعة الإسلامية بغزة - عمادة البحث العلمي والدراسات العليا, 2022)
هدف هذا البحث إلى بيان مفهوم الذوق العام وحدوده وضوابطه ومجالاته، ورد الطعون الموجهة إلى أحاديث الصحيحين بوجه عام بدعوى مخالفة الذوق العام، وحديث اغتسال موسى عليه السلام في ملا من بني إسرائيل الذي خرجه البخاري في الصحيح بوجه خاص، والتحقق من دعوى مخالفة هذا الحديث للذوق العام. وخلصت الدراسة إلى أن حدود الذوق العام وضوابطه لا تخلو أن تكون ضوابط منبثقة من القيم الدينية أو الإنسانية أو العقلية أو العادات والتقاليد أو الفطرة السليمة، أو ما هو متفق عليه عند القدوات وأصحاب الهيئات، وأن اغتسال موسى عليه السلام في مسير النهر لا يعد طعنا في ذوق موسى العام؛ فظروف الحياة القاسية التي كان يعيشها الناس في ذلك الوقت، وعدم وجود حمامات عامة هو ما جعل موسى عليه السلام يفعل ذلك، وأن اغتساله عريانا أمام ملا من بني إسرائيل لا يعد طعنا في موسى ولا في الرواية وليس منافيا للذوق العام؛ فهو نبي معصوم، وما وقع منه اقتضته الضرورة لإظهار براءته عليه السلام أمام قومه مما أتهم به. وتوصي الدراسة بعمل موسوعة علمية تعنى بجمع كل الشبهات حول السنة النبوية بوجه عام، وأحاديث الصحيحين بوجه خاص والرد عليها ردا علميا منهجيا بلغة يفهمها أهل العصر وتناسب عامة المثقفين. The aim of this research is to clarify the concept of public taste, its limits, controls and scopes, and to respond to the appeals against the hadiths of the two Sahihs in general, claiming that they violate public taste and the hadith of Moses, peace be upon him, washing in a gathering of the Children of Israel that al-Bukhari brought out in al-Sahih in particular, and verifying the claim that this hadith contradicts public taste. The study concluded that the limits of public taste and its controls are not without controls emanating from religious, human or mental values, customs and traditions, common sense, or what is agreed upon by role models and scholars. The harsh conditions of life that people were living at that time and the lack of public bathrooms is what made Moses, peace be upon him, do this, and if he was washed naked in front of a crowd of the Children of Israel, it is not considered an insult to Moses or the narration (hadith), and it is not contrary to public taste, for he is an infallible prophet and what happened from him necessity necessitated to show his innocence in front of his people of what he was accused of. The study recommends making a scientific encyclopedia concerned with collecting all the suspicions about the Prophet’s Sunnah and the hadiths of the two Sahihs in particular, and responding to them in a scientific and methodical way in a language that is understood by the people of the age and suitable for the general educated.
Keywords: الأحاديث النبوية -- حديث "اغتسال موسى" -- النقد الحديثي -- بنو إسرائيل -- الذوق العام